Kdo potrebuje strukturiran program izobraževanja svojcev bolnikov z okvaro hrbtenjače? - Puzić, Nataša (Rehabilitacija (Ljubljana), 2015)
Spinal cord lesion generates costs of health care for the individual as well as socio-economic costs. Persons after spinal cord lesion who are not independent need informal or formal assistance. Informal assistance is usually provided by family members, who become (or are already) physically and psychologically (over)burdened. An educational program for relatives that is implemented before a patient is discharged home from rehabilitation can reduce the burden and lower the incidence of secondary complications, and thus reduce healthcare costs, in the long-term. We started an educational program for relatives at our Department for rehabilitation of persons with spinal cord lesion three years ago. Like in other countries, we have been observing many advantages of such a program, which we are still improving.
Keywords: care; Education; independence; izobraževanje; nega; okvara hrbtenjače; rehabilitacija; Rehabilitation; samostojnost; Spinal Cord Compression; spinal cord lesion; vocational rehabilitation